ผลของโครงการปฏิบัติสมาธิเบื้องต้นต่อสัจจการแห่งตนตามทฤษฎีของมาสโลว์ - รณชัย ศิลากร (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
This research was a prospective descriptive study in one group. The objective of the study was to determine the effects of the initial practice of meditation programme toward self-actualization based on Maslow s theory. 291 subjects were randomized by simple random sampling. The instrument was questionnaire consisted of two parts: the demographic questionnaire, and the Personal Orientation Inventory (Thai version). The data was analyzed by SPSS for Windows. Statistics utilyzed were mean, percentage, standard deviation. T-test, One-way ANOVA, Post hoc analysis and Multiple linear regression. The results of this research indicated that there was the significant changes at p <0.05 in the overall self-actualization. including the self-actualization in the aspects of time competence, inner-directedness, self-actualizing value, spontaneity, self respect, self acceptance, acceptance of aggression and capacity for intimate contact but there was no statistically significant changes in the aspects of existentiality, feeling reactivity, nature of man-constructive and synergy . The related facters of the changes in self-actualization were gender, marital status and registration at significant level of p<0.05.